Influence of polishing in the roughness of a composite resin after contact with beer and ron: in vitro study - Ramirez Martinez, Valeria (2018)
Objective: Evaluate the surface roughness, weight and color of a composite resin, submitted to two finish and polish systems, after contact with beer and rum. Materials and methods: 63 BrilliantTM NG (COLTENE, USA) composite resin discs of 10 mm in diameter and 2 mm thick, after 24 hours of permanence in distilled water, randomly divided into three groups (n: 21) for polishing using Sof-flex (3M-USA) discs and fine-grained diamond burs (KG-Sorensen, Brazil) and third group without any procedure, for each sample the initial measurement was made in weight, roughness and color. The samples were subdivided into three subgroups and submerged in rum, beer or artificial saliva for 7 days; performing a new evaluation of weight, color and roughness. The data obtained were collected in Excel tables and statistically analyzed through Kruskal Wallis, Wilcoxon, Anova and Tukey tests. Results: The Tukey test, considering polishing systems and immersion substances, verified that polishing with diamond burs and contact with beer and rum produced changes in surface roughness (p = 0.00) with no influence on weight and color Results: The rum showed greater variation in surface roughness of composite resin, polishing with Sof-lex (3M-USA) discs caused less variation in values of roughness and color. No changes in weight.